Frequency of thyroid dysfunctions among Nigerian patients with vitiligo - P. Odum, Ehimen; Amadi, Collins (International Journal of Research in Medical Sciences, 2018)
Background: Vitiligo is associated with varying degrees of thyroid dysfunctions. This study was aimed to evaluate the thyroid dysfunctions in patients with vitiligo in Port Harcourt, Nigeria, West Africa. Methods: A retrospective, descriptive, cross-sectional analysis of thyroid function tests variables of 105 vitiligo patients who visited the Department of Chemical Pathology and Metabolic Medicine of the University of Port Harcourt Teaching Hospital between 1st January 2012 and 31st December 2016 was conducted. Records of age, sex, thyroid stimulating hormone, total thyroxine, total triiodothyronine was collected and analyzed using Shapiro-Wilk, descriptive, chi-square, Fisher’s exact, and Pearson’s tests. A statistical significance of p <0.05 was applied. Results: Females predominated among study cohort (61.9% female versus 38.1% male; p = 0.015). Most patients were less than 30 years old in both sexes. 26.7% (37 out of 105) had various degrees of thyroid dysfunctions. Among this 26.7% (37) with various thyroid dysfunctions, are 28 (75%) females and 9 (25%) males. These dysfunctions include primary hypothyroidism (6.7%), primary hyperthyroidism (1%), subclinical hypothyroidism (17.1%) and subclinical hyperthyroidism (1.9%), while the majority were euthyroid (73.3%). Subclinical hypothyroidism was the most common disorder (n = 18; 17.2%) with female preponderance (females n = 11; 61% versus males n = 7; 39%). Conclusions: This study confirms high frequency of thyroid dysfunctions among vitiligo patients. The culture of regular assessment of thyroid function should be mandatory among patients with vitiligo.